Biologics for eosinophilic granulomatosis with polyangiitis. Issue 1 (22nd February 2023) - Caminati, Marco; Maule, Matteo; Bello, Federica; Emmi, Giacomo
Abstract : Purpose of review: The link between severe asthma and eosinophilic granulomatosis with polyangiitis (EGPA) in terms of pathophysiological background, clinical manifestations and disease evolution has leaded to investigate the relevance of anti T2 monoclonal antibodies licensed for severe asthma patients as a treatment option for EGPA. The present review aimed to provide un update on EGPA pathophysiology and to critically summarize the most robust evidence coming from trials and real-life setting on the use of anti T2 biologics in EGPA patients. Recent findings: Mepolizumab, an anti-interleukin-5 monoclonal antibody, is the only biologic drug targeting eosinophilic inflammation currently approved for EGPA treatment at the dose of 300 mg/4 weeks. Its use is restricted by the American College of Rheumatology guidelines to specific diseases phases and severity grades. However the most appropriate mepolizumab positioning and dose is still under investigation in the real life practice, which is providing an increasing amount of evidence confirming its efficacy, alone or in combination with other options in different disease stages. The relevance of other monoclonal antibodies interfering with T2 inflammation, including omalizumab and benralizumab, is under investigation but the evidence is still scarce Summary: Taking into account the suboptimal medium-long term safety profile of conventional EGPA treatments, the opportunity of selectively targeting eosinophilic inflammation certainly represents a revolutionary approach. However, further real-word evidence is required to effectively position the new treatments in the light of the disease complexity, including different immunological drivers, and individual variability.